IMC Analysis of Tour de EnTeTe as NTT Sport Tourism Strategy - Agusta, Adellia; Umar, Zulkifli Djamaludin; Valentino, Yuan Elim; Nugraha, Mariano AT; Priscillia, Descorina (Moestopo International Review on Social, Humanities, and Sciences, 2026)
This study analyzes the strategic marketing communication of the Tour de EnTeTe sport tourism event in East Nusa Tenggara (NTT) Province through an Integrated Marketing Communication (IMC) framework, evaluating how integrated communication channels contribute to regional brand recognition and tourism revenue growth. A qualitative case study design was employed, supplemented by quantitative social media engagement analysis. Secondary data were gathered from official policy documents, government institutional reports, media publications, and Tour de EnTeTe's Instagram and YouTube accounts. Qualitative data were analyzed through thematic coding, while social media engagement was quantified using an engagement rate formula. The findings reveal that Tour de EnTeTe structurally adopted IMC elements; however, implementation remains fragmented due to weak inter-agency message consistency, limited dialogic interaction with global stakeholders, and NTT's archipelagic geographical constraints. Among five IMC indicators, personal selling emerged as the most dominant approach. Instagram engagement reached 6.17%, while YouTube generated 28,515 views. The study concludes that achieving sustainable sport tourism impact requires a strategic shift toward dialogic communicative action, reinforced by stronger inter-agency coordination, consistent messaging, and more robust digital analytics strategies to bridge the gap between policy intent and tourism outcomes.